1682. Health Resource Utilization in Patients with Complicated Urinary Tract Infections (cUTI) and Antibiotic Resistance or Treatment Failure: A Retrospective Database Analysis. (31st December 2020) - Sulham, Katherine; Reese, Jennifer
Abstract: Background: In the United States, urinary tract infections (UTIs) are predominately treated in the outpatient setting. Resistance to gram-negative bacteria has substantially increased in recent years, however, and many common oral treatment options continue to lose efficacy. As a result, patients may receive multiple courses of antibiotics at various outpatient settings and may ultimately require hospitalization. Here, we quantify health resource utilization and rate of hospitalization in patients with complicated UTI (cUTI). Methods: A retrospective study was performed in partnership with Komodo Health, Inc., using aggregate data from the Komodo Healthcare Map™ for cUTI-related events. Inclusion criteria: (1) 2+ UTI-related encounters within 35 days, beginning in 2017-2018, (2) clinical/coding features indicative of treatment failure or antibiotic resistance, or treatment with carbapenem or piperacillin/tazobactam.. Location of service, number of cUTI-related healthcare encounters, and rate of hospitalization following service location were quantified. Results: 1, 889, 216 cUTI patients with antibiotic resistance or treatment failure were identified; 1, 545, 559 were included in the site of care analysis. These patients incurred 8, 694, 236 cUTI-related healthcare encounters in 2017-2018. In 2017, among 1, 105, 459 patients, there were 385, 981 cUTI-related inpatient hospitalizations, 798, 574 emergency department (ED) visits, 285, 985 long-term care (LTC) stays, 147, 291 home health (HH) visits, and 2, 534, 083 other outpatient (OP) encounters. For patients with an ED visit, the mean number of visits was 1.67/patient; mean number of LTC, HH, and OP visits were 1.67, 3.07, and 2.97/patient, respectively. Of those who were hospitalized, 38% of patients were hospitalized following an ED encounter; hospitalization rates following LTC, HH, and OP visits were 30%, 43%, and 24%, respectively. The 30-day cUTI-related rehospitalization rate for inpatients was 12%. 2018 data was similar. Conclusion: cUTI is associated with substantial health resource utilization, the majority of which occurs in the outpatient setting. Disclosures: Katherine Sulham, MPH, Spero Therapeutics (Independent Contractor) Jennifer Reese, PharmD, Spero Therapeutics (Employee)